RADIO SOURCE DIRECTION FINDING IN WIDE FREQUENCY BAND USING CIRCULAR ANTENNA ARRAY - Maya E. Shevchenko; Victor N. Malyshev; Dilara N. Fayzullina (Известия высших учебных заведений России: Радиоэлектроника)
For the VHF broadband direction finder, coherent and incoherent direction finding algorithms for switched and non-switched connection of the antenna array (AR) to receiving device in single-signal and multi-signal direction finding modes are developed and investigated.Their synthesis is based on the methods of space-time theory of radio systems. Numerical calculation of the direction finding characteristics of the algorithms for different number of antenna array elements determines the operating range upper limiting frequency, in which this configuration provides single-value estimates of the azimuth and elevation angle. Statistical simulation modeling shows that for an odd number of antennas, the antenna array amplitudephase response is unique in a wider frequency band than for an even number of antennas. Due to this MUSIC based property applied in the space of antenna array elements, direction finding algorithm is developed for wide frequency band with several signals overlapping in frequency, with switched and non-switched AR connection to a radio receiver. It is shown that the use of ESPRIT and MUSIC methods in free-space diagram does not allow for direction finding in a wide frequency band with the antenna array fixed configuration. The results of the field studies of the developed algorithms are presented for the single-signal and multi-signal modes of operation, software and hardware implemented in the VHF radio direction finder. A comparative analysis of the developed algorithms with the known APs with fixed configuration is performed. It is shown that with the same AR configuration, it is the direction finding algorithm that determines the frequency range in which the direction finding is unique.